it has to do with completing the square.
in Algebra 1 Answers by

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:
To avoid this verification in future, please log in or register.

3 Answers

x^2 + 12x + 4 = 0
(x^2 + 12x) + 4 = 0
(x + 6)^2 - 36 + 4 = 0
(x + 6)^2 - 32 = 0
(x + 6)^2 = 32
x + 6 = sqrt(32) or = -sqrt(32)
x = -6 + sqrt(32) or x = -6 - sqrt(32)
by
Cannot be factored
by

x^2 + 12x + 4 = 0
(x^2 + 12x) + 4 = 0
(x + 6)^2 - 36 + 4 = 0
(x + 6)^2 - 32 = 0
(x + 6)^2 = 32
x + 6 = sqrt(32) or = -sqrt(32)
x = -6 + sqrt(32) or x = -6 - sqrt(32) by lila its correct!!!!!

by

Related questions

1 answer
1 answer
1 answer
Welcome to MathHomeworkAnswers.org, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
83,678 questions
88,568 answers
1,985 comments
5,802 users